2013
DOI: 10.7314/apjcp.2013.14.3.1895
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Practice among Malaysian University Students

Abstract: Background: It is well established that a healthy lifestyle is of benefit in the prevention of diseases such as cancer and promotion of well-being. Therefore, the objective of this study was to determine lifestyle practice and associated factors among university students in Malaysia. Materials and Methods: A cross sectional study was conducted over six months from November 2011 until May 2012 among the students from the Management and Science University. This study was approved by its ethical committee , the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 65 publications
6
29
1
Order By: Relevance
“…So during stressful time smokers believe that smoking reduces their stress. Previous researchers had provided various treatments for smoking cessation, but based on this present study results, this study recommends that anti-smoking treatment should target modifying the irrational belief about the benefits of smoking cigarettes as it reinforces the smoking behavior among students (Ozturk et al, 2011;Al-naggar, 2013).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…So during stressful time smokers believe that smoking reduces their stress. Previous researchers had provided various treatments for smoking cessation, but based on this present study results, this study recommends that anti-smoking treatment should target modifying the irrational belief about the benefits of smoking cigarettes as it reinforces the smoking behavior among students (Ozturk et al, 2011;Al-naggar, 2013).…”
Section: Discussionmentioning
confidence: 77%
“…Lim 2013(Lim et al, 2013 identified that 59.3% of malesaged from 21 to 30 smokes cigarettes comparedto the other age groups in Malaysia. The prevalence of smoking was higher among male (41.2%) than female (17.5%) in one of the private university in Malaysia (Al-Naggar et al, 2013). There may be many female smokers as like male in Asian counties, but female smokers from Asian countries are reluctant to admit to the researchers that they are smokers (Zawahir et al, 2013).…”
Section: Psychological Problems and Psychosocial Predictors Of Cigarementioning
confidence: 98%
“…In a study among the Malaysian University students by AlNaggar et al also reported females were about two times more likely to be physically inactive than males and many studies have shown lower physical active and physical inactive is pandemic especially among younger adults and a leading cause of death in the world. [15][16][17] Compared to their inactive peers, children and adolescents doing at least 60 minutes of moderate-to vigorous-intensity physical activity daily have higher levels of cardiorespiratory fitness, muscular endurance and strength. Documented health benefits of regular physical activity among young people also include reduced body fat, more favourable cardiovascular and metabolic disease risk profiles, enhanced bone health, and reduced symptoms of anxiety and depression.…”
mentioning
confidence: 99%
“…When the literature is reviewed, few studies focusing on the influence of the cigarette smoking status of grandparents on the cigarette smoking by children and young people are seen, and these studies conclude that smoking by grandparents smoking has no direct influence on cigarette smoking by children and young people (Kalesan et al, 2006;Brook et al, 2012;Vandewater et al, 2014). Again, Studies emphasize that smoking by grandparents influences smoking by parents, that children whose parents smoke cigarette, on the other hand, smoke cigarette more, and that smoking by grandparents has an indirect influence on smoking by children and young people (Ohido et al, 2001;Kalesan et al, 2006;Bektas et al, 2010b;Al-naggaret al, 2011;Golbasi et al, 2011;Ozturk et al, 2011;Azhar and Alsayed, 2012;Brook et al, 2012;Ulgen et al, 2012;Al-Naggar et al, 2013;Jeganathan et al, 2013;Ozturk et al, 2013;Vandewater et al, 2014;). The findings of the current study are consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%